2021
DOI: 10.3390/diagnostics11020163
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Ultrasound Shear Wave Elastography as a Non-Invasive Biomarker in Myotonia

Abstract: Myotonia, i.e., delayed muscle relaxation in certain hereditary muscle disorders, can be assessed quantitatively using different techniques ranging from force measurements to electrodiagnostics. Ultrasound shear wave elastography (SWE) has been proposed as a novel tool in biomechanics and neuromuscular medicine for the non-invasive estimation of muscle elasticity and, indirectly, muscle force. The aim of this study is to provide ‘proof-of-principle’ that SWE allows a quantitative measurement of the duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…This conversion relies on the assumption that the medium is purely elastic without viscous components and perfect isotropy. 29 Muscle tissue is, however, not purely elastic and is not isotropic 17 and therefore, the conversion assumptions are violated.…”
Section: Resultsmentioning
confidence: 99%
“…This conversion relies on the assumption that the medium is purely elastic without viscous components and perfect isotropy. 29 Muscle tissue is, however, not purely elastic and is not isotropic 17 and therefore, the conversion assumptions are violated.…”
Section: Resultsmentioning
confidence: 99%
“…Despite such challenges in relating the measured shear wave speed to muscle stiffness, previous studies denoted the promising clinical use of SWE in muscle diagnostics and therapeutic monitoring, e.g., for patients with myositis, stroke, cerebral palsy or multiple sclerosis [ 18 ]. SWE was claimed to be a biomarker in myotonia as the muscle relaxing time estimated using SWE was similar to those obtained with mechanical dynamometers [ 19 ]. Increased shear wave speed under passive conditions of the biceps brachii muscle (BB) was found in patients with Parkinson’s Disease [ 20 ] and it was shown that SWE output correlates with joint rigidity [ 21 ].…”
Section: Introductionmentioning
confidence: 86%
“…Some reported increased SWV with age [29,30], while some reported a decreased value [24,31,32]. More recent studies [5,20] have led to the assumption that the differences regarding age and sex could remain negligible within the respective SD, though those clinical characteristics should be taken more into account in an extended, larger study. (3) We only correlated the SWV with clinical assessments according to the MDS-UPDRS.…”
Section: Limitationsmentioning
confidence: 99%
“…For comparison, 10 healthy control subjects (HC) were examined. Matching by age and sex was omitted as in comparable SWE studies [20], among other reasons because the primary aim of this study was to show a longitudinal effect within PD, not to compare the results of PD patients to those of HC. All participants were over the age of 18 and provided informed consent.…”
Section: Subjectsmentioning
confidence: 99%